2021
DOI: 10.3389/fonc.2020.576901
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Scoring System of Intrahepatic Cholangiocarcinoma With Machine Learning Basing on Real-World Data

Abstract: Background and ObjectivesCurrently, the prognostic performance of the staging systems proposed by the 8th edition of the American Joint Committee on Cancer (AJCC 8th) and the Liver Cancer Study Group of Japan (LCSGJ) in resectable intrahepatic cholangiocarcinoma (ICC) remains controversial. The aim of this study was to use machine learning techniques to modify existing ICC staging strategies based on clinical data and to demonstrate the accuracy and discrimination capacity in prognostic prediction.Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“… 6 9 , 18 44 Twenty-six studies 6 9 , 18 31 , 33 38 , 42 , 44 developed their own original prediction models (Supplemental Table 1, http://links.lww.com/AOSO/A246 ), and 5 studies 32 , 39 41 , 43 conducted external validations on previously published models ( Table 1 ). Eighteen studies (69%) published nomograms, 8 , 18 , 19 , 21 30 , 33 , 36 , 37 , 42 , 44 7 studies (27%) published scoring systems, 6 , 9 , 20 , 31 , 34 , 35 , 38 and 1 study (4%) published an online calculator. 7 All 26 original models were developed using a retrospective cohort, and 9 studies (35%) used single-center data to develop the models.…”
Section: Resultsmentioning
confidence: 99%
“… 6 9 , 18 44 Twenty-six studies 6 9 , 18 31 , 33 38 , 42 , 44 developed their own original prediction models (Supplemental Table 1, http://links.lww.com/AOSO/A246 ), and 5 studies 32 , 39 41 , 43 conducted external validations on previously published models ( Table 1 ). Eighteen studies (69%) published nomograms, 8 , 18 , 19 , 21 30 , 33 , 36 , 37 , 42 , 44 7 studies (27%) published scoring systems, 6 , 9 , 20 , 31 , 34 , 35 , 38 and 1 study (4%) published an online calculator. 7 All 26 original models were developed using a retrospective cohort, and 9 studies (35%) used single-center data to develop the models.…”
Section: Resultsmentioning
confidence: 99%
“…While most machine learning-based models have been applied for cancer diagnosis and risk assessment, their application in survival prediction has been limited 28 . Furthermore, most machine learning-based survival analyses have been based on gene expression data from databases such as The Cancer Genome Atlas (TCGA) 18 , 29 or multi-omics data 30 , with few studies utilizing high-dimensional real-world survival data 31 , 32 , thus limiting their applicability to the current practice. Recent research by Abuhelwa et al 10 demonstrated the feasibility and effectiveness of machine learning-based approaches for survival prediction in urothelial cancer patients treated with atezolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative biomarkers, including CA 19-9, CRP, and CAR (ratio between CRP and albumin), were used for predicting OS and RFS (91). on XGBoost, RF, and GBDT to evaluate the prognosis by biomarkers, with a C-index of 0.693 (94). The psoas muscle index, defined as the area of the psoas muscle at the L3 vertebra level divided by the squared body height, combined with the features of tumor burden and hepatic reserve in ANN, with an AUC of 0.89 in the 1-year survival prediction in ICC, was significantly higher than the Fudan score (95,96).…”
Section: Ai and Prognosismentioning
confidence: 99%